2018
DOI: 10.22159/ajpcr.2018.v11i6.25325
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Paracasei Hii01 Mediated Fermentation of Syzygium Cumini L. Fruits: Assessment of Changes in Phenolic Content and Antioxidant Capacity

Abstract: Objective: Syzygium cumini L. fruits are reported for several pharmacological applications and winemaking. The present study was conducted to develop and analyze the phytochemical content, and antioxidant properties of lactic acid bacteria mediated fermented S. cumini fruit juice (FSJ). Methods:The pH of FSJ was measured by pH meter, and total acidity was calculated by titration method. The Folin-Ciocalteu colorimetric method was employed to assess the total phenolic content (TPC), and antioxidant properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
5
1
1
Order By: Relevance
“…and Sirin et al ., 39 reported similar results for DPPH radical‐scavenging activity, around 30% higher than the control. Nevertheless, total polyphenol concentrations seemed to be lower than the average compared to results reached by other LAB 40 …”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…and Sirin et al ., 39 reported similar results for DPPH radical‐scavenging activity, around 30% higher than the control. Nevertheless, total polyphenol concentrations seemed to be lower than the average compared to results reached by other LAB 40 …”
Section: Resultscontrasting
confidence: 66%
“…Nevertheless, total polyphenol concentrations seemed to be lower than the average compared to results reached by other LAB. 40 LAB CFS in the biopreservation of red grapes Figure 1 shows the results for the percentage of fruits contaminated per day. Figure 2 The results of the number of viable spores per gram of grapes are shown in Fig.…”
Section: Identification Of Antifungal Compoundsmentioning
confidence: 99%
“…Sirilun et al [94] observed an increase in total phenolic content and antioxidant activity of Syzygium cumini L. fruit juice after fermentation with Lb. paracasei strain HII01.…”
Section: Resultsmentioning
confidence: 99%
“…An opposite phenomenon was noted in studies of fruits. Sirilun et al 59 reported an increase in the total phenolic content and the antioxidant activity in Syzygium cumini L. fruit juice fermented by Lb. paracasei strain HII01, and Bujna et al 60 observed an increase in the amount of phenols and antioxidant activity in apricot juice.…”
Section: Vegetablesmentioning
confidence: 99%